Stability of the magnetosonic wave in a cometary multi-ion plasma. Issue 10 (15th May 2017) - Sreekala, G.; Varghese, Anu; Jayakumar, Neethu; Michael, Manesh; Sebastian, Sijo; Venugopal, Chandu
Abstract: A generalized dispersion relation of the magnetosonic wave in a four component plasma consisting of electrons and hydrogen ions of solar origin and positively and negatively charged oxygen ions of cometary origin has been derived by using the Vlasov-Maxwell kinetic model. Parallel to the magnetic field, the hydrogen and electron components are modeled by a drifting Maxwellian distribution; perpendicular to the magnetic field, we use a loss cone type distribution obtained by the subtraction of two Maxwellian distributions having different temperatures. The effect of change in the drift velocity of streaming components and number densities and temperatures of each species in driving the instability has been analyzed both analytically and numerically. For typical parameters at comet Halley, we find that both positively and negatively charged oxygen ions can drive the wave unstable.